Noticing grammar in L2 writing and problem-solving strategies - Geist, Monika (Studies in Second Language Learning and Teaching, 2017)
Noticing plays an important role for second language acquisition. Since the formulation of the output hypothesis (Swain, 1985), it has been proven that producing output can lead to noticing. Studies on noticing have revealed little focus on grammar, and an in-depth investigation of grammar noticing has not been conducted so far. Studies into problemsolving strategies applied to resolve noticing in writing have provided differing classifications. The current study investigates the noticing of ten young learners (15 to 16 years) of L2 English while performing a writing task, with a special focus on grammar. The problem-solving strategies these learners applied are analyzed. With regard to the linguistic areas, results suggest that verb forms, especially the use of modals, and the choice of prepositions, are the main issues encountered in morphology. In syntax, learners mainly dealt with the length of sentences and the ways of connecting clauses. Learners relied on their intuition and existing knowledge, common sense and rephrasing as grammar problem-solving strategies. These results open a new area of study into noticing grammar and suggest some implications for teaching.